Design of Lu2O3-reinforced Cf/SiC-ZrB2-ZrC ultra-high temperature ceramic matrix composites: Wetting and interfacial reactivity by ZrSi2 based alloys. Issue 5 (May 2021) - Tatarko, Peter; Valenza, Fabrizio; Ünsal, Hakan; Kovalčíková, Alexandra; Sedláček, Jaroslav; Šajgalík, Pavol
Abstract: The wettability and infiltration of molten ZrSi2 and ZrSi2 -Lu2 O3 alloys into Cf /SiC and B4 C-infiltrated Cf /SiC composites were investigated to understand the interfacial interactions that occur during the development of Cf /SiC-ZrC and Cf /SiC-ZrB2 -ZrC-Lu2 O3 materials. A significant evaporation of Si from the liquid affected the wetting behaviour of the alloy when tested in a vacuum at 1670 °C. The better wetting and spreading of the alloy over the surface was observed for the composites with lower overall porosity (12 %). On the other hand, the formation of an outer dense layer, followed up by the uniform infiltrated region up to ∼ 1 mm was observed for the Cf /SiC with higher porosity (21 %). The infiltrated alloy reacted with SiC matrix to form ZrC or with B4 C-infiltrated SiC matrix to form ZrB2 -ZrC-SiC. The Lu2 O3 particles were not wetted by the melt, and were pushed away of the reaction zone by the solidification front.